2018
DOI: 10.3847/1538-4357/aad187
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Active Region Filament Driven By a Series of Jets

Abstract: We present a formation process of a filament in active region NOAA 12574 during the period from 2016 August 11 to 12. Combining the observations of GONG Hα, Hida spectrum and SDO/AIA 304 A, the formation process of the filament is studied. It is found that cool material (T ∼ 10 4 K) is ejected by a series of jets originating from the western foot-point of the filament. Simultaneously, the magnetic flux emerged from the photosphere in the vicinity of the western foot-point of the filament. These observations su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 110 publications
6
33
1
Order By: Relevance
“…It is widely accepted that the material of the filaments or prominences should originate from the low atmosphere (chromosphere) (Pikel'Ner 1971;Zirker et al 1994;Liu et al 2005;Yang et al 2016;Wang et al 2018). In this paper, we also confirm that the mass of the filament was extracted from the low atmosphere instead of the corona.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is widely accepted that the material of the filaments or prominences should originate from the low atmosphere (chromosphere) (Pikel'Ner 1971;Zirker et al 1994;Liu et al 2005;Yang et al 2016;Wang et al 2018). In this paper, we also confirm that the mass of the filament was extracted from the low atmosphere instead of the corona.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…Furthermore, the only few observation evidences could be captured to supported to the this models ). On the other hand, many observations are more likely to support the injection models which rely on magnetic reconnection in the low atmosphere to propel cool plasma to typical filament height (Wang 1999;Liu et al 2005;Zou et al 2017;Wang et al 2018). In this paper, we supplied a observational evidence that the filament material can be supplied by a series of jets related to the new emerging magnetic field, which again verify the injection model.…”
Section: Conclusion and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have proposed various models for explaining the mass formation of filaments, such as the injection model (Wang 1999), levitation model (Rust & Kumar 1994), and the evaporation-condensation model (Engvold & Jensen 1977;Xia et al 2011Xia et al , 2012Xia et al , 2014. Liu et al (2005) found that the cool filament mass can be provided the chromospheric jets from one end along the filament main axis (see also Wang et al (2018)), in which the authors did not explain how the cool jet mass injected into the filament channel. The event studied in the present paper clearly exhibited that the two-sided loop jet injected mass into the overlying LF from the below by the magnetic reconnection between the jet and the magnetic field of the filament's cavity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the observation of Liu et al (2005), they suggested that erupting Hα surges may directly link to the replenishment of filament materials. Furthermore, more and more observational evidences support this scenario (Zou et al 2016(Zou et al , 2017Wang et al 2018). All of these works indicate that a chromospheric eruption can be a source origin of filament replenishment.…”
mentioning
confidence: 90%